'The Deliberative and Dynamic model for engineering education curriculum renewal' - Hargroves, Charlie; Desha, Cheryl (2015)
Sustainability issues will shape what students do in their future careers, especially within built environment professions. Yet many institutions struggle to adapt programs and coursework to reflect this. Responding to a need for guidance, this book provides a practical resource to quickly – and effectively – update curriculum to meet the emergent sustainability context. The authors use their experiences in engineering education and insights from colleagues and institutions around the world to provide tools to address common institutional challenges and to make the most of emerging opportunities. The book begins by exploring the rationale for action, discussing why curriculum renewal has been challenging to-date and identifying urgent drivers for change. It then presents a new model for curriculum renewal to deal with these challenges, from course and program design through to stakeholder engagement and organisational considerations. The model shows what educational leaders are beginning to practise: a whole-of-system approach to timely program design and review. The book uses the model to detail practical ways to move forward, including creating a strategy, identifying graduate attributes, mapping learning outcomes, auditing the program, updating coursework and implementing the renewed curriculum. With extensive case study material from around the world, this resource will assist institutions – from department heads to program convenors – to cost-effectively align offerings with present and future educational demands.